Antibacterial Therapy of Tularemia: Current Status and Prospects - I. A. Shchipeleva; E. I. Markovskaya; O. F. Kretenchuk (Антибиотики и Химиотерапия)
The review article includes summarized literature data on experimental evaluation of Francisella tularensis susceptibility to existing antibiotics, and their effectiveness in treatment of tularemia in humans population. The data on ways to improve the effectiveness of some antibacterial drugs that show reduced activity in treatment of tularemia infection are presented. The range of studies aimed at creating modern and more effective antibiotics with new mechanisms of action is defined. A number of methods for modifying variants of the already known groups of antibacterial drugs, as well as ways of prevention or limitation of antibiotic resistance formation in F.tularensis are described.